LEGAL STATUS OF PATENT ATTORNEYS, TRADE MARK ATTORNEYS UNDER THE UNITED KINGDOM LAW - Kmetyk, Khrystyna V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the author makes an attempt to research the legal status of patent attorneys, trade mark attorneys in the intellectual property right of the United Kingdom using the method of induction, systematic approach, formal legal methods. Analyzing the problem the author separates and gives legal description of different types of patent attorneys and trade mark attorneys as advisors in the field of intellectual property right of the United Kingdom. The main provisions of the Rules of Conduct for Patent Attorneys, Trade Mark Attorneys and Other Regulated Persons (2015) (also well-known as Code of Conduct) are considered in detailed. Results: this research provides an opportunity to broaden the understanding of the institution of patent attorneys, trade mark attorneys in the intellectual property right of the United Kingdom and thus include this knowledge in the domestic research on intellectual property right. The obtained results will have a positive impact on the reform of the institute of representatives in the field of intellectual property in Ukraine in order to ensure its effectiveness and relevance to the challenges of the present. Conclusions: all types of patent attorneys and trade mark attorneys as advisors in the field of intellectual property right of the United Kingdom are well-educated professionals in all areas of intellectual property. They are able to advise on a wide range of technical and commercial issues in this field. Implementing a similar diversity of advisors in the field of intellectual property right of Ukraine will have a positive impact on the reform of the institute of representatives in the field of intellectual property in Ukraine in order to ensure its effectiveness and relevance to the challenges of the present.